A Dramaturgy of Translation: The Brussels City Theatre as a Site of Negotiation between Language Policy and Practice - Denolf, Eline (Text Matters: A Journal of Literature, Theory and Culture, 2025)
State-funded city theatres play an important role in keeping a finger on the pulse of society. As porous institutions that act as meeting places between artists and citizens, they can present themselves as reflexive or subversive voices. The combination of Brussels’ idiosyncratic sociolinguistic situation and its artist-driven performing arts landscape provides an exceptional context for encounter between the wealth of language communities and heterogeneous audiences. In this article, I examine how the Royal Flemish Theatre (KVS) uses this bottom-up dynamic to reflect the city’s urban multilingualism both on stage and in its outreach strategies. I consider the institution’s exemplary role in structurally embedding a trilingual translation policy, and its latitude in relation to politically conditioned requirements in a city where Dutch is increasingly becoming a minority language. This way, I demonstrate that, far beyond catering for the Flemish minority, KVS’s language and translation policy, as well as its principles, align with a future-oriented political project based in actual language practices. Furthermore, I highlight the particular role of the in-house “city dramaturg,” who probes the urban fabric and guards the institution’s vision while navigating the conditions imposed by funding bodies. It is argued that, by destabilising long-standing linguistic and cultural relations, KVS functions as a translation site, a shared space of debate to negotiate language relations and translation practices.